The stage and the school - Ommanney, Katharine Anne; Schanker, Harry H. (St. Louis, Missouri : Webster Division, McGraw-Hill, 1972)
This latest edition of the first dramatics textbook to be used extensively at the secondary level is designed to meet the changing needs of high school students without losing the fundamentals.
Part One. Understanding the drama -- Part Two. Interpreting the drama -- Part Three. appreciating the drama -- Part Four. Producing the drama.
Includes index.
Keywords: AMATEUR THEATER